The Diagnostic Value of Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography for the Detection of Surgical Site Infection after Spine Surgery. Issue 10 (15th May 2021) - Segawa, Tomohide; Koga, Hisashi; Oshina, Masahito; Fukushima, Masayoshi; Inanami, Hirohiko
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: Retrospective case series. Objective: The purpose of this study was to assess the diagnostic yield of fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (F-18 FDG PET/CT) for surgical site infection (SSI) after spine surgery. Summary of Background Data: Diagnosis of SSI in the spine based on F-18 FDG PET/CT requires experienced nuclear medical physicians for a detailed analysis of F-18 FDG distribution pattern. It has also been reported that increases in the maximal standardized uptake values of F-18 FDG (SUVmax ) closely correlated with SSI, suggesting potential of more objective and quantitative diagnosis. Methods: We assessed the diagnostic yield of F-18 FDG PET/CT (pattern-based diagnosis by nuclear medical physicians and SUVmax -based diagnosis) for SSI in 52 subjects who underwent spine surgery. The 52 subjects included 11 nonimplant and 41 implant cases. F-18 FDG PET/CT was performed in 33 and 19 cases in early (≤12 weeks after the surgery) and late (>12 weeks) phases, respectively. The final diagnosis of SSI was based on the results of pathogen identification, plain radiography, and CT and/or magnetic resonance imaging or response to antibiotics and/or reoperation. Results: SUVmax -based diagnosis was performed with a cut off value of 5.0 as determined by receiver operating characteristic analysis. Both pattern-based and SUVmax -based diagnoses demonstrated excellent diagnostic yields with high sensitivity (97% and 90%), specificity (100% and 100%), and accuracy (98% and 94%). High diagnostic yields (accuracy of ≥90%) were consistently observed irrespective of presence or absence of implantation or interval between surgery and F-18 FDG PET/CT. Conclusion: F-18 FDG PET/CT can be the procedure of choice for investigation of SSI in the spine when other imaging fails to provide a definitive diagnosis. Level of Evidence: 4